2005
DOI: 10.1677/jme.1.01717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inactivating mutations on phosphorylation and internalization of the human VPAC2 receptor

Abstract: The VPAC 2 receptor, as all members of the G-protein-coupled receptor (GPCR)-B family, has two highly conserved motifs in the third intracellular (IC 3 ) loop: a lysine and a leucine located at the amino-terminus and two basic residues separated by a leucine and an alanine at the carboxyl-terminus. This study evaluates the involvement of those conserved amino acid sequences in VPAC 2 signal transduction and regulation. The residues were mutated into alanine and mutants were expressed in Chinese hamster ovary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In VPAC 2 receptors, L 310 located in the proximal part of IC3 contributes to Gαs activation and the proximal part of IC3 (R 325 and K 328 ) is involved in both Gαs and Gα16 coupling. The combined mutations of these three amino acids generates an inactive VPAC 2 receptor with respect to [Ca 2 + ] i increase and adenylate cyclase activation (Langer et al, 2005). …”
Section: Molecular Mechanisms Involved In Vpac/g Protein Binding and mentioning
confidence: 99%
See 1 more Smart Citation
“…In VPAC 2 receptors, L 310 located in the proximal part of IC3 contributes to Gαs activation and the proximal part of IC3 (R 325 and K 328 ) is involved in both Gαs and Gα16 coupling. The combined mutations of these three amino acids generates an inactive VPAC 2 receptor with respect to [Ca 2 + ] i increase and adenylate cyclase activation (Langer et al, 2005). …”
Section: Molecular Mechanisms Involved In Vpac/g Protein Binding and mentioning
confidence: 99%
“…Absence of inhibitory effect of PKA and PKC inhibitors (Langer et al, 2005; Langlet et al, 2005), use of dominant negative GRK and GRK over-expression experiments (Shetzline et al, 2002; Huang et al, 2007), suggest that GRK are the main kinases involved in VIP receptors phosphorylation. VPAC 1 receptor phosphorylation induces β-arrestin translocation to cell membrane, however, over-expression of β-arrestin in HEK 293 cells only causes a minor decrease in cAMP, suggesting VPAC 1 desensitization may occur through an arrestin-independent mechanism (Shetzline et al, 2002).…”
Section: Regulation Of Vpac Receptors Activitymentioning
confidence: 99%
“…Within the third intracellular loop, mutation of a central lysine-leucine motif of the opossum parathyroid hormone receptor, rat GLP1 receptor, and human VPAC1 and VPAC2 receptors, analogous to the human secretin receptor residues Lys 302 -Leu 303 (ICL3A), results in defects in agonist-stimulated cAMP production, calcium mobilization, and ligand binding to varying degrees (1,7,25,38,45,62). In the present work, replacing these residues with alanines in the human secretin receptor resulted in normal ligand binding and calcium signaling, but reduced cAMP responses.…”
Section: Discussionmentioning
confidence: 99%
“…In ICL2, Arg241, and Lys242 have been reported to be critical for the inositol phosphate (IP 3 ) signaling in many secretin GPCR members (Mathi et al 1997, Langer et al 2005. However, mutation analysis showed that this motif did not affect the calcium responses in human SCTR (Garcia et al 2012).…”
Section: Motifs For Signal Transductionmentioning
confidence: 99%